Pemanfaatan Framework CodeIgniter dalam Pengembangan Sistem Informasi Pendataan Laporan Praktik Kerja Lapangan dengan Metode Rapid Application Development (RAD) - Sari, Yolen Perdana; Prihandono, Rivaldo Galuh (Scientia Sacra: Jurnal Sains, Teknologi dan Masyarakat, 2022)
Field Work Practices (PKL) or known as Industrial Work Practices (PRAKERIN) are a means for vocational high school students (SMK) to apply the knowledge they have learned and add insight into the world of work they will face in the future. One school must have more than one major, for distribution, data management and internship information are quite difficult without a well-integrated system. For this reason, an information system for data collection of internship reports is needed starting from placement, monitoring and evaluation. This system was developed using the Rapid Application Development (RAD) method. This method focuses on developing applications quickly through repetition and repeated feedback resulting in a very short development cycle. The results of the development of this system can of course help the school in terms of data collection and distribution of prakerin information to heads of departments, supervisors, and students.